(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In our proposed system is identifying disease based on symptoms. This system will allow users to get instant guidance on their health issues through an intelligent health care android app. in this system we will cover all disease. The system is fed with various symptoms and the disease associated with those symptoms. The system allows user to enter their symptoms. It then processes user’s symptoms to check for various diseases that could be associated with it. Notifications are automatically generated and send to doctors and admin of system when patient view diseases and associated symptoms. Here we use some intelligent algorithms to guess the most accurate diseases that could be associated with patient’s symptoms. In doctor module when doctor login to the system doctor can view his patient details and also view the notifications generated by system. This system will provide proper guidance when the user specifies the symptoms of his illness. System will also suggest the doctors for proper treatment and patient can online take appointment with the doctor. Additionally for general disease the system will provide Ranking for General Physician, nearer to the user area.